Arthroscopic Lateral Collateral Ligament Repair. (3rd August 2016) - Kim, Jeong Woo; Yi, Young; Kim, Tae Kyun; Kang, Hong Je; Kim, Jong Yun; Lee, Jong Myoung; Bae, Kyu Hwan; Joo, Min Su
Abstract : Background: Lateral ulnar collateral ligament injury following unstable elbow dislocation can induce posterolateral rotatory instability that requires surgery. The aim of this study was to determine the effectiveness of arthroscopic repair of the lateral collateral ligament (LCL) complex in an unstable elbow joint. Methods: The study group consisted of 13 patients who experienced posterolateral rotatory instability after an unstable elbow dislocation with an injury to the lateral ulnar collateral ligament. The diagnosis was confirmed with computed tomography (CT), magnetic resonance imaging (MRI), and physical examination. The patients underwent arthroscopically assisted surgery between May 2011 and January 2013 and were followed for a minimum of 18 months postoperatively. Coronoid and/or radial head fractures combined with the ligament injury were treated through an arthroscopic technique. Range of motion, pain, outcomes according to the Mayo Elbow Performance Score (MEPS) and Nestor grading system, and surgical complications were evaluated. CT and MRI were performed at 3 months postoperatively, and isometric muscle strength was measured at the time of final follow-up. Results: At the time of final follow-up, at a minimum of 18 months, all 13 patients reported complete resolution of the instability and average (and standard deviation) extension of 3° ± 1°, flexion of 138° ± 6°, supination of 88° ± 5°, and pronation of 87° ± 6. The mean MEPS was 92 points and, according to this validated outcome score, the results were rated as excellent in 12 patients and good in 1 patient. According to the Nestor grading system, the results were rated as excellent in 11 patients and good in 2. Complete healing was seen on the 3-month follow-up MRI in 12 patients; however, 1 patient had mild widening of the radiocapitellar joint space with incomplete healing but no instability symptoms. All patients demonstrated normal strength on elbow flexion, extension, pronation, and supination at the final follow-up visit. Conclusions: Arthroscopic repair of the LCL complex in patients with posterolateral rotatory instability after an unstable elbow dislocation, with or without an intra-articular fracture, is an alternative treatment option for restoring elbow stability and achieving satisfactory clinical and radiographic results. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.